A Listening Wind : Native Literature from the Southeast - Haag, Marcia, 1951- (Book collections on Project MUSE., 2016)
"This collection of stories from several different tribal traditions in the American Southeast includes introductory essays showing how they fit into Native American religious and philosophical systems."--Provided by publisher.